Peningkatan Hasil Belajar IPA Melalui Model Problem Based Learning Berbantu Media Canva pada Siswa Kelas V SDN Pandeanlamper 03 - Mentari Dharma Santi; Farida Nursyahidah; Aryo Andri Nugroho; Estiyani Estiyani (Journal on Education, 2023)
This study aims to improve science learning outcomes for fifth grade students at SDN Pandeanlamper 03 using the Problem Based Learning (PBL) model with the help of Canva media. This study uses a class action research method with a research design in the form of two cycles. Each cycle applies four steps according to Kemmis and M.K. Taggart in Arikunto (2010), namely planning (planning), implementation of action (action), observation (observation) and reflection (thinking). The dependent variable is student learning outcomes and the independent variable is the Canva-assisted Problem Based Learning model. Data collection methods used include interviews, observation, tests and documentation with quantitative and qualitative analysis techniques. The research subjects were fifth grade students at SDN Pandeanlamper 03 consisting of 28 students. The results of the study show that the application of the PBL model with the help of Canva media can improve student learning outcomes in science subjects. In Cycle I, the percentage of students who successfully completed the subject was 57%, while in Cycle II it increased to 79%. This increase in learning outcomes meets the success indicator of 70%. In addition, observations also show that students are more active and involved in the learning process when using the PBL model with the help of Canva media.